Emergency Ultrasound Training Program in Guyana: Systematic Credentialing Process in a Resource‐limited Setting. Issue 2 (21st December 2018) - Rupp, Jordan D.; Jagjit, Sri Devi; Ferre, Robinson M.
Abstract: Ultrasound has become an important skill for emergency physicians. Ultrasound is more crucial in resource‐limited settings where diagnostic testing may not be as timely or available at all. In 2015, an emergency medicine ultrasound curriculum was implemented at Georgetown Public Hospital Corporation in Georgetown, Guyana. Implementing an ultrasound‐training curriculum in Guyana had four main challenges: limited ultrasound equipment, lack of informational technology infrastructure to record and review ultrasound examinations, availability of local emergency ultrasound expertise, and competing educational needs within the curriculum. These challenges were met with creative solutions and the formation of a formalized curriculum and credentialing process. The experience of creating the program is described along with the curriculum, credentialing process, and plan for sustainability. Since implementation, every graduating resident has displayed competency on final assessment.